Morphological peculiarities of nematodes Oswaldocruzia filiformis quantity in moor frog in Northern regions of Kazakhstan as the indicator of herbal cover (Experimental biology, 2020)
Nematode Oswaldocruzia filiformis occurring in wide circle of cold-blooded tetrapods develops with obligate larval stages in environment, needing grass plants, and in this connection this parasite may be the indicator of near-water areas and plant cover.During snowless period of 2005-2017 years in flood-plain landscapes of Irtysh river in Pavlodar region 2084 exemplars of moor frog were caught and subjected to helminthological autopsy. Material from 1984-1987 years included 593 exemplars of moor frog.Long-year dynamics of absolute sizes of nematodes O.filiformis from 2005 till 2017 years showed almost two-fold diversity of linear sizes. Minimal sizes in flood-plain landscapes of Irtysh river was fixed in summer 2005 (middle male length was 5,7493±0,1477 mm, width 0,1456±0,0042mm; sizes of females was  8,3506±0,2556 and 0,1851±0,0045 mm correspondently). Nematode females reached to maximal sizes in 2015 (14,4915±0,1431 mm of length and 0,21024±0,00192 mm of width). Maximal middle males’ length 7,77096±0,0975 mm was observed in 2017, maximal means of males’ body width were recorded in 2015-2016 years(0,1719 и 0,1715 mm). Highest females’ sizes of O.filiformis from moor frog was registered in 2006 (20,6 mm of length and 0,3 mm of width), with small middle nematodes sizes. Maximal male’s length (12,35 mm) was observed in 2013, maximal width (0,25 mm) – in 2012.In the population of large adult moor frogs from Birzhankol’ lake in 2004-2005 years (Kazakh Melkosopochnik) O.filiformis females reached till 21 mm of length and 0,35 mm of width, males – till 13,0 and 0,25 mm correspondently. In the low ground near “Yablon’ka” garden the slow growth of young frogs and comparatively small length and large width of O.filiformis (medium male’s length was 6,25625±0,4257, width 0,1781±0,0074 mm; medium female’s length 8,83±0,2791, width – 0,27±0,0255 mm) were observed, which were caused by organic pollution leading to the depression as hosts as helminthes. Among the factors limiting the linear sizes of helminthes we can call hosts’ sizes, interspecific and intraspecific competition between helminthes.Key words: moor frog, nematode Oswaldocruzia filiformis, seasonal dynamics of infection indicators, flood plain, regime of river